Sınıf Öğretmeni Yetiştirme Programları ve Sanat Eğitimi - Ayşe ÇAKIR İLHAN (Ankara Üniversitesi Eğitim Bilimleri Fakültesi Dergisi)
In this paper, it has been sought that what has been expected from the theoreical and practical modules in Art Education for the trainees in Türkish Education System are the expectation sufficient and relavent? Are the classroom teachers able to teach art education during the first five years of basic education? And should they teach?